VALUE RELEVANCE OF OTHER COMPREHENSIVE INCOME AND FAIR VALUE MEASUREMENT - RĂPAN CLAUDIA MIHAELA; BANŢA VIOREL COSTIN; MANEA ANDREIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2022)
Fair value measurement raises challenges among the Company’s management and users of financial information. The disclosure of other comprehensive income (OCI) that includes information regarding fair value measurement provides value relevance for all interested stakeholders. The current empirical study explores the value relevance of “other comprehensive income” by analyzing the relationship between the share price, OCI, and the variance of the gain/loss of revaluation reserve for the financial period 2017- 2021 in the case of companies listed on European Stock Exchange markets (Italy, France,Spain and Germany). The results of the study conclude that there is an association between other comprehensive income and the share prices in the context of the revaluation of the fixed assets